Challenges and Strategies for Strengthening the Link Between Public Audit and Industrial Policy in Ghana - Afadzinu, Sewornu Kobla; Koltai, Judit (Journal of Posthumanism, 2025)
This study explores the integration of public audit within Ghana’s industrial policy framework, focusing on the challenges faced by the Ghana Audit Service (GAS) in influencing policy effectiveness and accountability. Drawing on governance and accountability theory, resource dependence theory, inter-organizational coordination theory, and policy feedback theory, the study examines the institutional, resource-based, and procedural factors that affect GAS’s ability to drive policy improvement. A qualitative document analysis approach was employed, reviewing audit reports, policy documents, and legislative texts from 2013 to 2022. Key findings reveal that limited resources, a lack of standardized performance indicators, inadequate inter-agency coordination, and weak accountability mechanisms hinder GAS’s capacity to impact policy outcomes effectively. To address these challenges, the study proposes strategies to enhance resource allocation for GAS, establish formalized coordination mechanisms, develop clear performance metrics, and implement robust accountability structures. These recommendations aim to create a responsive, transparent governance framework that enables GAS to support evidence-based policy adjustments. This research contributes to the literature on public audit and governance in emerging economies, underscoring the role of integrated audit-policy frameworks in fostering accountable, effective industrial policies.